1996
DOI: 10.1017/s135772980001465x
|View full text |Cite
|
Sign up to set email alerts
|

A two-diet system andad libitumlactation feeding of the sow 1. Sow performance

Abstract: Effects of a two-diet system combined withad libitumlactation feeding of sows on food consumption, sow live weight (LW), backfat depth, condition scoring, rebreeding interval, symptoms of agalactia and culling were studied on 60 sows followed for four parities. Feeding regimes were: CR, conventional i.e. restricted during gestation and lactation; SA, a simplified diet offered at a restricted level during gestation and a conventional dietad libitumduring lactation; CA, conventional during gestation and the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 24 publications
3
20
1
1
Order By: Relevance
“…These results are in agreement with results from previous studies (Neil et al, 1996;Mahan, 1998). Milk production is another important concern in the management of lactating sows because it is directly related to litter performance.It is also known that parity is one of factors affecting milk yield during lactation Noblet et al, 1998;Eissen et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with results from previous studies (Neil et al, 1996;Mahan, 1998). Milk production is another important concern in the management of lactating sows because it is directly related to litter performance.It is also known that parity is one of factors affecting milk yield during lactation Noblet et al, 1998;Eissen et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…As seen in Table 4 the sows mobilized fat during the whole lactation period. Apparently, the intake of energy was not sufficient to cover the energy requirement for milk production which is a problem in modern production as pointed out by Neil et al (1996) and Cole (1990). The present studies suggest that the energy supply rather than the protein supply is the limiting factor for milk production.…”
Section: Discussionmentioning
confidence: 99%
“…The litter size has increased considerably over the last decades, and the size of the sows has increased as well (Moustsen et al, 2004). The voluntary feed intake does not always meet the requirements of the sow for energy and nutrients, resulting in mobilization of body tissues (Neil et al, 1996), which may affect future reproduction negatively (King et al, 1984). The selection for lean pigs has further charged the ability of sows to mobilize body fat during lactation and reduced the voluntary feed intake (Cole, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…An adequate water and feed intake is important for sow health (Neil et al, 1996), performance and reproduction (Koketsu et al, 1997). Several studies have shown that an increased feed intake decreases body weight loss, increases litter performance and backfat depth (Eissen et al, 2003;Le Cozler et al, 1999;Peng et al, 2007;Prunier et al, 1997).…”
Section: Introductionmentioning
confidence: 99%